Hubungan Rasio SpO2/FiO2 dengan Rasio PaO2/FiO2 Pada Pasien Acute Respiratory Distress Syndrome (ARDS) di ICU RSUP H. Adam Malik - Pramono, Agus; Lubis, Andriamuri Primaputra; Ihsan, Muhammad (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2024)
Introduction: The PaO2/FiO2 (P/F) ratio is the main choice for invasively assessing ARDS. The SpO2/FiO2 (S/F) ratio can be used as a noninvasive oxygenation parameter in ARDS patients. This study was conducted to determine the relationship between the SpO2/FiO2 ratio and the PaO2/FiO2 ratio. Methods: This study was observational with a cross-sectional research method to see the relationship between the SpO2/FiO2 ratio and the PaO2/FiO2 ratio in ARDS patients. The total sample was 29 intubated ICU patients diagnosed with ARDS. This study excluded patients with congestive heart disease, anemia, and systolic blood pressure less than 90 mmHg. Result: A linear regression analysis was obtained between the PaO2/FiO2 and the SpO2/FiO2 ratio with a relationship coefficient of 0,955 and p-value of 0,001. A relationship was found between the S/F ratio and the P/F ratio in assessing the severity of ARDS (p-value less than 0.05). Conclusion: Assessment analysis of the SpO2/FiO2 ratio and the PaO2/FiO2 ratio has a relationship so that it can be used as a predictor of ARDS.